Identity in Education - Sánchez-Casal, S. author. aut Link
XV, 278 p.
Keywords: This volume explores the impact of social identity on teaching and learning. The contributors argue, from the perspective of diverse disciplinary and educational contexts, that mobilizing identities in the classroom is a necessary part of progressive educators' efforts to transform knowledge-making and to create a more just and democratic society.